Manajemen Mutu Pembelajaran Matematika Dalam Mempersiapkan Asesmen Standarisasi Pendidikan Daerah - Hayati, Siti Rokh; Mulyono, Rahmat (Universitas Sarjanawiyata Tamansiswa, 2024)
The purposes of this research are quality management of Mathematics learning; the role of Mathematics learning quality management in preparing ASPD; Mathematics learning results for class IX students at SMPN 1 Playen Gunungkidul. This type of research is qualitative research that uses interview, observation, and documentation techniques. The research was conducted at SMPN 1 Playen. Researchers collect, reduce, present data, and draw conclusions. The results of the research show that the quality management of mathematics learning for class IX students at SMPN 1 Playen, including planning, organizing, implementing, as well as monitoring and evaluating, has gone well. Planning for the quality of learning begins with preparing the school curriculum and program, organizing by drawing up a decree on the division of tasks and lesson schedules, implementing learning in accordance with the planning, monitoring and evaluation carried out by the school principal and the implementation team at least once a semester. The role of quality management in mathematics learning is shown by the teacher's role in implementing learning in the classroom. The teacher makes a lesson plan, implements learning according to the lesson plan, the teacher uses various learning methods to help increase students' understanding of ASPD, students' mathematics learning outcomes are shown by the average Try Out and ASPD results, namely 35.00; 36.00; 35.95 for try out and 34.03 for ASPD. The ASPD results are not yet on target because students have not mastered basic mathematical concepts, students are less able to understand the questions, and students' motivation to learn is still lacking.